Evolution of specialized toxin arsenals in a bacterial symbiont of arthropods - Moore, Logan D; Ballinger, Matthew J (The ISME Journal, 2025)
Bacteria commonly deploy toxic proteins that act with specificity on target molecules to support invasion and improve survival in competitive environments. Many toxin-encoding bacteria have evolved into host-associated defensive partnerships, in which they use toxins to improve host survival during infection. The stability of these relationships requires that symbiont toxins target diverse parasites while minimizing damage to the host. We investigate the specificity of a group of ribosome-targeting toxins (ribosome-inactivating proteins) encoded by heritable Spiroplasma symbionts that contribute to defense against parasite infection in fruit fly hosts. Using Escherichia coli to express five divergent copies of this toxin, we show that distantly related members of the family all retain the ability to inactivate ribosomes by adenine cleavage at the α-sarcin/ricin loop, the enzymatic hallmark of RIPs. However, when exposed to live insect and fungal cells, ribosome inactivation varies across the five toxins, suggesting cellular recognition or localization play a role in target specificity. To identify toxin domains required for specificity, we removed rapidly evolving “accessory” domains from two toxins. Both truncated toxins exhibit significantly increased activity on purified ribosomes in vitro, suggesting one role of accessory domains is to reduce toxicity, which may help protect hosts from collateral damage. One of the truncated toxins also showed significantly reduced inactivation of cellular ribosomes in vivo, indicating a role for accessory domains in cell specificity. Together, these data reveal a mechanism for symbiont discrimination between hosts and parasites and highlight how dynamic toxin evolution can contribute to stability and novelty in defensive symbiosis.